Prolegomena. Problems and Perspectives of Historical Network Research and Ancient History - Rollinger, Christian (Journal of Historical Network Research, 2020)
This contribution reviews previous contributions to ancient history by means of social network analysis and historical network research. In trying to ascertain common methodological challenges and identifying strategies of overcoming them, it attempts to provide guidance for future research projects.